Enhanced phenylpropanoid metabolism underlies resistance to Fusarium oxysporum f. sp. vasinfectum race 4 infection in the cotton cultivar Pima-S6 (Gossypium barbadense L.) - Ojeda-Rivera, Jonathan Odilón; Ulloa, Mauricio; Pérez-Zavala, Francisco G.; Nájera-González, Héctor-Rogelio; Roberts, Philip A.; Yong-Villalobos, Lenin; Yadav, Himanshu; Chávez Montes, Ricardo A.; Herrera-Estrella, Luis; Lopez-Arredondo, Damar (Frontiers in Genetics, 2024)
Fusarium oxysporum f. sp. vasinfectum (FOV) race 4 (FOV4) is a highly pathogenic soil-borne fungus responsible for Fusarium wilt in cotton (Gossypium spp.). Pima (G. barbadense L.) cotton, which is highly valued for its fiber quality, has been shown to be more susceptible to this pathogen than Upland (G. hirsutum L.) cotton. Still, some Pima cultivars present resistance to FOV4 infection. To gain insights into the FOV4-resistance mechanism, we performed a comparative transcriptional and metabolomic analysis between FOV4-susceptible and FOV4-resistant Pima cotton entries. We found that an enhanced root phenylpropanoid metabolism in the resistant Pima-S6 cultivar determines FOV4-resistance. Gene-ontology enrichment of phenylpropanoid biosynthesis and metabolism categories correlated with the accumulation of secondary metabolites in Pima-S6 roots, specifically esculetin, a coumarin that inhibits the growth of Fusarium. Genes involved with phenylpropanoid biosynthesis and metabolism are interesting research prospects for FOV4-disease resistance and breeding approaches of other cotton cultivars of economic relevance.